A meta‐analysis of third wave mindfulness‐based cognitive behavioral therapies for older people. (11th November 2016) - Kishita, Naoko; Takei, Yuko; Stewart, Ian
Abstract : Objectives: The aim of this study is to review the effectiveness of third wave mindfulness‐based cognitive behavioral therapies (CBTs) for depressive or anxiety symptomatology in older adults across a wide range of physical and psychological conditions. Methods: Electronic literature databases were searched for articles, and random‐effects meta‐analysis was conducted. Results: Ten studies met the inclusion criteria, of which nine reported the efficacy of interventions on depressive symptoms and seven on anxiety symptoms. Effect‐size estimates suggested that mindfulness‐based CBT is moderately effective on depressive symptoms in older adults ( g = 0.55). The results demonstrated a similar level of overall effect size for anxiety symptoms ( g = 0.58). However, there was a large heterogeneity, and publication bias was evident in studies reporting outcomes on anxiety symptoms, and thus, this observed efficacy for late‐life anxiety may not be robust. The quality of the included studies varied. Only one study used an active psychological control condition. There were a limited number of studies that used an intent‐to‐treat (last observation carried forward method) analysis and reported appropriate methods for clinical trials (e.g., treatment‐integrity reporting). Conclusions: Third wave mindfulness‐based CBT may be robust in particular for depressive symptoms in older adults. We recommend that future studies (i) conduct randomized controlled trials with intent‐to‐treat to compare mindfulness‐based CBT with other types of psychotherapy in older people and (ii) improve study quality by using appropriate methods for checking treatment adherence, randomization, and blinding of assessors. Copyright © 2016 John Wiley & Sons, Ltd.